Técnicas de Neurorrafia: Estudio Experimental Estereológico Axonal Comparativo - Boer, Nagib Pezati; Batigalia, Fernando; Viterbo, Fausto [UNESP]; Faleiros, Humberto Regis de Paula; Ramos, Rogério Rodrigo; Simonato, Luciana Estevam; Boer, Luis Fernando Ricci (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2015)
There is a great variety of injuries that affect peripheral nerves derived from acquired or congenital degenerative diseases affecting the central nervous system that cause loss of sensorimotor functions. The objective of this work was to perform an endto- side or side-to-side experimental axonal stereological study in order to compare volume density of axons, endouneuro and myelin sheath (and muscle mass) in peroneal and tibial nerves, with anastomosis contact from 0.25 cm to 0.50 cm. After approval of the Ethics Committe, 20 male Wistar rats were divided into four groups of five rats each (G1= end-to-side neurorrhaphy; G2= side-to-side neurorrhaphy of 0.25 cm; G3= side-to-side neurorrhaphy of 0 cm and G4= Control of normality). After 180 days, fragments of peroneal and tibial nerves were collected for histological and stereological study. In comparative stereological experimental study between neurorraphies, the volume density of axons, myelin sheath of tibial and fibular nerves, as well as the post-surgical muscle mass, remains the same in end-to-side and side-to-side neurorraphies, regardless of contact area of anastomosis. It can be inferred, as surgical repair options, both end-to-side neurorrhaphy to recover and prevents atrophy of the endplate as side-to-side neurorraphy that is independent of the distance between the nerve stumps.
Neurorrhaphy techniques: Comparative stereological and experimental axonal study
Keywords: Axon; Endoneurium; Myelin sheath; Neurorraphy; Reinnervation; Stereolog0y